Analysis of the Effect of Loading on the Transformers Usage Time - Ritonga, Adi Syahputra; Muthalib, Muchlis Abdul; Daud, Muhammad; Lubis, Hamdi Akmal; Pokhrel, Biswas Babu; Phuyal, Sudip; Gohatre, Umakant B. (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2021)
The reliability and stability of the system in the operation of the electric power system is very important, in order to provide comfort in service to consumers. The transformer is a very important component in the electric power system, because it is used as a voltage adjuster for the load being served. This study discusses the effect of loading and temperature on the life shrinkage of 36/60 MVA power transformers in block 3 and block 4 carried out at PT. PJB UBJ O&M PLTMG Arun Lhokseumawe, Aceh. From the calculation results after 4 years the transformer operates, if the transformer is given a 100% load, the transformer will experience an age difference of 2.52 p.u/day so that it has a remaining life for of 10 years. As for the transformer that is given a load of 90%, the transformer will experience an age difference of 1.44 p.u/day so that it has a remaining life to perform operations for another 18 years. Then for a transformer that is given a load of 80%, the transformer will experience an age difference of 0.67 p.u/day so that it will have a remaining life to carry out the operation again for another 38 years. From the above calculation, the origin of the temperature obtained for the ONAN type of cooler in block 3 is 0.71 p.u/day and in block 4 it is 0.70 p.u/day. While the ONAF type of cooler in block 3 is 0.004 p.u/day and in block 4 it is 0.005 p.u/day. This is in accordance with the regulation SPLN50/1982 regarding transformer life shrinkage.